Student Learning in Interdisciplinary Team-Taught Courses Centered on a “Big Idea” - Baker, Megan; Pollard, John (Journal of Interdisciplinary Studies in Education, 2021)
The increased demand for more integrative curricular opportunities for post-secondary students has resulted in the exploration of new curricular approaches which center on approaching today’s ‘big ideas’ or ‘grand challenges’ from multiple disciplinary viewpoints. This article documents one such course designed to promote interdisciplinary approaches using a team teaching co-convening model at the University of Arizona’s Honors College. Results indicate that students affirm the value of interdisciplinary education and perceive this collaborative and co-instructed model as beneficial to their learning. This curricular model was found to have positive implications for the roll of collaborative classroom pedagogies for bolstering learner interest, fostering perspective-taking behaviors, and creating a classroom environment in which students perceive their intellectual contributions as valued.